2009
DOI: 10.1038/eye.2009.198
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding and association with refractive error in young Singapore Chinese children

Abstract: Purpose The objective of this study was to investigate an association between spherical refractive error and breastfeeding. Methods Strabismus, amblyopia, and refractive errors in Singaporean preschoolers (STARS) is a cross-sectional population-based study of 3009 Chinese children aged 6-72 months conducted between June 2006 and September 2008 in Singapore. Parents were asked about the history of breastfeeding in face-to-face interviews. Children without cycloplegia or without refraction assessment were exclud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 10 publications
3
27
0
1
Order By: Relevance
“…Some previous studies suggested that infants with breastfeeding will have better vision and be less likely to be myopic in later life than those with formula feeding [38,39]. A study in young Singapore Chinese children showed that breastfeeding was associated with more positive spherical equivalent refraction [40]. However, another two studies did not find any significant relationship between feeding patterns and visual acuity and spherical equivalent refraction [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies suggested that infants with breastfeeding will have better vision and be less likely to be myopic in later life than those with formula feeding [38,39]. A study in young Singapore Chinese children showed that breastfeeding was associated with more positive spherical equivalent refraction [40]. However, another two studies did not find any significant relationship between feeding patterns and visual acuity and spherical equivalent refraction [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Several previous observational studies have suggested better visual outcomes in infancy and early childhood among children who were breastfed compared to those formula-fed. 9 , 11 , 28 , 29 However, not all such studies have been as supportive; some suggest no effect 13 or associations that might be partially or wholly explained by residual confounding. 25 Our finding of similar levels of low vision amongst children from maternity hospitals and clinics randomized to breastfeeding promotion or continued standard practice suggests that longer duration and more exclusive breastfeeding has little effect in patterning vision outcomes into late childhood.…”
Section: Discussionmentioning
confidence: 99%
“…10 Some evidence suggests that breastfeeding promotes visual development, and hence less susceptibility to ametropia (refractive error), 9 , 11 , 12 findings that have been attributed to the long-chain n-3 polyunsaturated fatty acids (LCPUFAs) present in breast milk. However, more recent survey evidence has been less supportive, 13 and although LCPUFAs occur in high concentrations in retinal photoreceptors, trials comparing LCPUFA supplemented with unsupplemented formula have yielded equivocal results. 14 , 15 Inconsistencies may be due to differences in LCPUFA exposure, statistical power or, in observational studies, the degree of adjustment for confounders.…”
mentioning
confidence: 99%
“…While several local studies have examined breastfeeding [ 16 , 21 , 22 , 23 ], picky eating [ 24 ] and parenting practices [ 14 ], little research has been done on infant feeding practices in Asian populations. To our knowledge, this study is the first to provide data on infant feeding practices in a multi-ethnic cohort.…”
Section: Discussionmentioning
confidence: 99%